Performance of TFET and FinFET devices applied to current mirrors for different dimensions and temperatures. (11th March 2016) - Martino, M D V; Martino, J A; Agopian, P G D; Vandooren, A; Rooyackers, R; Simoen, E; Thean, A; Claeys, C
Abstract: The goal of this work is to compare the behavior of a current mirror designed with Tunnel-FET and FinFET devices. The suitability of these technologies in such a basic circuit has been analyzed focusing on the susceptibility to output bias conditions, dimensions mismatching and temperature variations. In the experimental part, results revealed a similar channel width dependence, but a much more relevant channel length dependence for the circuit with FinFETs. Meanwhile, varying the output bias, it was observed that a wider range of output drain voltage results in a suitable mirrored current for the circuit with tunnel field effect transistors (TFETs). In the second part of this work, numerical simulations have been performed for different temperatures. The opposite trends observed for higher temperatures could be justified based on the different dominant transport mechanism in each circuit. Globally, current mirrors with TFETs presented the best results, with lower output current susceptibility to dimensions mismatching and temperature variation.